Nutritional Assessment of Sagurimi: Innovative Dry Noodles from Sago Flour and Nile Tilapia (Oreochromis niloticus) for Stunted Children - Resti, Nina; Syauqy, Ahmad; Anjani, Gemala; Mexitalia, Maria; Jaswir, Irwandi; Afifah, Diana Nur (Indonesian Food Science and Technology Journal, 2025)
Chronic malnutrition at crucial stages of a child's development can result in stunting, a serious public health concern. The goal of this study was to create high-protein dry noodles. The study used several methods, such as the oven method for measuring water content, the dry ashing method for ash, the Soxhlet method for fat, the Kjeldahl method for protein, the difference method for carbohydrates, the enzymatic method for fiber, the Atwater factor for energy content, the Na₂EDTA complexometric titration for calcium, the atomic absorption spectroscopy (AAS) for iron, the in vitro method for measuring protein digestibility, and the DPPH method for measuring antioxidants. Three formulations, namely F1 (20:20:60), F2 (30:40:30), and F3 (40:30:30), were developed to represent different ratios of sago flour, wheat flour, and fish meal. F1 exhibited the highest nutritional values, particularly in protein (24.60 g), fat (29.19 g), calcium (479.57 mg), iron (26.11 mg), and antioxidant activity (35.79%). The best formulation was selected using the Index of Effectiveness method, combining rankings of nutrient content and sensory acceptability. Due to its higher amount of wheat flour, F2 had the largest calorie (494.04 kcal) and carbohydrate content (33.24 g). Because there was more sago flour in F3, it had the most fiber (14.98 g). These results demonstrate the potential for creating novel, regionally sourced foods, such as Sagurimi made from Nile tilapia, to lessen childhood stunting. In order to evaluate acceptability and efficacy, future research should concentrate on clinical trials and sensory evaluation.